Identification and functional characterization of CYP4V2 genetic variants exhibiting decreased activity of lauric acid metabolism - Jarrar, Yazun Bashir; Shin, Jae‐Gook; Lee, Su‐Jun (Annals of human genetics, 2020)
The objectives of the present study were to identify CYP4V2 genetic variants and characterize their functional consequences. A total of 26CYP4V2 genetic variants were identified, including seven novel variants in 60 randomly selected healthy subjects. Six protein‐coding variants were studied, including three novel variants (L22V, R287T, and G410C) and three previously reported variants (R36S, Q259K, and H331P). The cDNA sequences encoding each amino acid variant and the wild‐type CYP4V2 protein were cloned into the pcDNA/PDEST40 expression vector and transfected into eukaryotic 293T cells for overexpression of the CYP4V2 coding variants. CYP4V2 H331P and CYP4V2 G410C exhibited significant decreases in activity for lauric acid oxidation (20–30% of wild‐type activity), when compared to the wildtype, which was correlated with low expression of CYP4V2 H331P and G410C substituted proteins. The other four CYP4V2 amino variants were comparable to wild‐type CYP4V2 for lauric acid metabolism. The CYP4V2 H331P and G410C substitutions were predicted to cause a structural change through in silico analysis. In conclusion, the present study provides functional information about CYP4V2 genetic variants. These findings will be valuable for interpreting individual variations in phenotypes associated with CYP4V2 function in the clinical setting.